Factors influencing the use of mechanisms for coordinating healthcare levels in Colombia (2019)
Objective: To analyse the factors influencing the use of mechanisms for the clinical coordination of two Colombian public healthcare networks’ healthcare levels in Bogotá from the main social actors’ perspective. Method: This was a descriptive-interpretative, qualitative study of two public healthcare networks. Discussion groups and semi-structured interviews were used for collecting information. The approach involved two-stage theoretical sampling of a selection of centres operating at different healthcare levels and a selection of informants, including managers (n = 19), healthcare employees (n = 23) and administrative staff (n = 20). Content analysis involved adopting a mixed method approach for generating categories, segmented by network, informant group and topic. Results: Both networks had few mechanisms for enabling the clinical coordination of healthcare levels; information transfer mechanisms predominated and clinical management coordination mechanisms only dealt with maternal-perinatal care. Organisational factor-related complications were found regarding their use: lack of time, staff turnover, administrative use and technological deficiency. Employee/staff-related difficulties were due to lack of interest. These factors directly affected coordination with limited information transfer, patient follow-up and healthcare quality (diagnosis and treatment delays). Conclusions: The results highlighted the limited use of clinical coordination mechanisms in both public healthcare networks studied here, with problems in their use. Changes are required that affect directly organisational factors (time for coordination and working conditions) and professional factors (attitudes towards collaborative work). © 2019